Elements of Historical Personal Identity Construction of Finnish-Speaking Students - Taivalantti, Tanja; Norppa, Johanna; Löfström, Jan (MDPI, 2025)
In this paper, the constructions of historical personal identity of Finnish-speaking students are analysed. The students participated in a larger study of historical narratives and identities, carried out in 2020 in two schools in Finland and in one European School outside Finland. In the mixed-method study, sixty-one students were interviewed and given writing and drawing assignments on historical identity. In this paper, the students’ visual representations of their personal historical identity and its relationship with wider official history are analysed. The aim is to increase understanding of how 14–16-year-old students visualise and articulate their historical personal identity constructions and the historical elements they use in negotiating this identity. The findings suggest that the students integrate personal and historical social narratives in diverse ways but that the majority of them find it challenging to connect their personal family history with the wider official history. Only twelve students made the connection. In addition to presenting the results for the whole group of students, the visual representations of two selected students are discussed in more detail so as to highlight the difference in the approaches to historical personal identity construction among the students.